2019
DOI: 10.1088/1361-648x/ab2217
|View full text |Cite
|
Sign up to set email alerts
|

Selective probing of magnetic order on Tb and Ir sites in stuffed Tb2Ir2O7  using resonant x-ray scattering

Abstract: We study the magnetic structure of the "stuffed" (Tb-rich) pyrochlore iridate Tb2+xIr2−xO7−y, using resonant elastic x-ray scattering (REXS). In order to disentangle contributions from Tb and Ir magnetic sublattices, experiments were performed at the Ir L3 and Tb M5 edges, which provide selective sensitivity to Ir 5d and Tb 4f magnetic moments, respectively. At the Ir L3 edge, we found the onset of long-range k = 0 magnetic order below T Ir N ∼ 71 K, consistent with the expected signal of all-in all-out (AIAO)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Since chemical off-stoichiometry in Eu 2+ x Ir 2– x O 7– y cause the nonmagnetic Eu 3+ ions stuffing onto Ir sites or antisite Eu/Ir occupations, , the introduced nonmagnetic defects will dilute the Ir 4+ moments, leading to the instability of AIAO order and reduced net FM components within DWs. These behaviors are consistent with recent resonant X-ray scattering on Tb 2+ x Ir 2– x O 7– y single crystals, where off-stoichiometry reduces both T N and effective moments of Ir 4+ sublattices. On the other side, less magnetic disorders in stoichiometric crystals help to stabilize the AIAO domain state and related DWs, responsible for the enhanced ferromagnetism.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Since chemical off-stoichiometry in Eu 2+ x Ir 2– x O 7– y cause the nonmagnetic Eu 3+ ions stuffing onto Ir sites or antisite Eu/Ir occupations, , the introduced nonmagnetic defects will dilute the Ir 4+ moments, leading to the instability of AIAO order and reduced net FM components within DWs. These behaviors are consistent with recent resonant X-ray scattering on Tb 2+ x Ir 2– x O 7– y single crystals, where off-stoichiometry reduces both T N and effective moments of Ir 4+ sublattices. On the other side, less magnetic disorders in stoichiometric crystals help to stabilize the AIAO domain state and related DWs, responsible for the enhanced ferromagnetism.…”
Section: Resultssupporting
confidence: 91%
“…The most stoichiometric crystal exhibits the largest H EB , M shift , and coercive field ( H C ) in all measured temperatures (Figure a–c), indicative of its strongest exchange coupling between the AIAO domain and its DWs. Considering the nonmagnetic dilution effect on Ir 4+ sublattices in off-stoichiometric Eu 2+ x Ir 2– x O 7– y , , the reduced FM components in DWs and concomitant unstable AIAO order will weaken the FM/AFM exchange coupling, producing smaller EB effects in off-stoichiometric crystals. As shown in Figure c, H C shows nonmonotonic temperature dependence with maxima at temperature ( T p ).…”
Section: Resultsmentioning
confidence: 99%
“…5 (a)). A similar dependence of the RXS signal on the field strength has been observed by Donnerer et al 25 in Tb 2 Ir 2 O 7 . Finally, we observed that modifying the field direction from α ∼ 45 • towards a fully out-of-plane configuration, i.e.…”
Section: Resultssupporting
confidence: 86%
“…The correlation lengths at 5 K are ∼ 27 Å and ∼ 32 Å for the induced ortho and CDW orders, respectively. In various transition metal oxides 24,25 and other multinary rare-earth containing systems, such as the rare-earth tritellurides 26 or synthetic multilayer systems 27 , the formation of induced order on the rareearth sublattice has already been observed. Likewise, in DyBCO, the temperature-dependent resonant scattering intensity at the Dy edge decays quickly with temperature, reflecting the temperature-dependent susceptibility of the Dy sublattice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrochlore iridates of formula A 2 B 2 O 7 (A= rare Earth elements; and B= Ir) are one of the materials with a significant magnetic frustration owing to Coulomb correlation and spin-orbit coupling [25][26][27]. Among these materials we find: Pr 2 Ir 2 O 7 , Tb 2 Ir 2 O 7 , Eu 2 Ir 2 O 7 , Y 2 Ir 2−x Cr x O 7 [28][29][30], etc According to the findings on these materials, the lanthanides A and their interactions with the moments B = Ir frequently result in intriguing physical properties. These materials have been used in a variety of applications, including magnetic refrigeration.…”
Section: Introductionmentioning
confidence: 92%